2012
DOI: 10.7860/jcdr/2012/4685.2623
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometerical Association of the Craniofacial Dysmorphology with Schizophrenia

Abstract: Background: Dysmorphology is more concentrated in the craniofacial region of Schizophrenic Patients. So, an early anthropometric assessment of the physical dimensions of the cranium and the face may indicate a potential clue of Schizophrenia. Aims:To study the craniofacial dysmorphology in schizophrenic patients and in healthy controls of the Agra region and to find out whether its evaluation could be used as a tool in the early diagnosis of schizophrenia. Setting and Design:This was a case-control, cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Bacanu et al [28] explained that the height and schizophrenia disorder are likely to have mostly overlapping genetic causes of discordant effect. Body height was used to relativize the value of head circumference, and this ratio was signifi-cantly higher in a study by Mishra et al [29], which is also in line with results of Huang et al [8]. Our study confirmed these findings only in male population -circumference relative to body height has been revealed as a significantly greater ratio in male schizophrenia patients, but without any statistically significant difference in the total sample.…”
Section: Discussionsupporting
confidence: 92%
“…Bacanu et al [28] explained that the height and schizophrenia disorder are likely to have mostly overlapping genetic causes of discordant effect. Body height was used to relativize the value of head circumference, and this ratio was signifi-cantly higher in a study by Mishra et al [29], which is also in line with results of Huang et al [8]. Our study confirmed these findings only in male population -circumference relative to body height has been revealed as a significantly greater ratio in male schizophrenia patients, but without any statistically significant difference in the total sample.…”
Section: Discussionsupporting
confidence: 92%
“…A study established links between posterior cranial fossa dysmorphogenesis and major depression (20). Studies also linked skull dysmorphogenesis with schizophrenia (10,11,17), bipolar illness (12) and other psychoses (18).…”
Section: Literary Evidences Linking Etiogenesis Of Neuropsychiatric Dmentioning
confidence: 99%
“…Plausibly, these variations accumulated in the long course of evolution (33)(34)(35), through assimilation of co-variances (34,35) and epigenetic changes (36) in the gross and genetic structure of a population respectively, implied morphological integration (34,37). The inclusion of variations in the skull components in the course of evolution might have subjected a population to acquire and propagate multiple errors at molecular level (3) and to express these as aberrant genotypes and phenotypes (38), setting basis for etiogenesis of certain neuropsychiatric disorders (10,12,18,7).…”
Section: Evolutionary Aspectmentioning
confidence: 99%
See 2 more Smart Citations